Comparative Study of Fatty Acid Composition of Gametes, Embryos and Larvae of Rainbow Trout, Oncorhynchus mykiss - Harlioglu, Ayse Gul (Zoological Soc Pakistan, 2017)
The fatty acid compositions of unfertilized eggs, semen, fertilized eggs, eyed embryo, yolk-sac larvae and absorbed yolk-sac larvae were investigated in rainbow trout (O. mykiss). The polyunsaturated fatty acids (PUFA) were found the highest followed by monounsaturated fatty acids (MUFA) and saturated fatty acids (SFA) in the unfertilized eggs. On the other hand, PUFA was the highest followed by SFA and MUFA in the semen. The proportions of the some fatty acids, such as C14:0, C16:1n-7, C18:0, C18:1n-9, C18:2n-6, C18:3n-3, C20:2n-6, C20:3n-6, C20:4n-6, C22:6n-3 remained stable from fertilized eggs to yolk-sac larvae, therefore no significant (P>0.05) difference was observed in these fatty acids between fertilized eggs and yolk-sac larvae. Nevertheless, significant (P<0.05) decreases were observed in C14:0, C16:1n-7, C18:1n-9, C18:2n-6, C18:3n-3, C20:1n-9, C20:2n-6, C20:3n-6 between fertilized eggs and absorbed yolk sac larvae. Moreover, a significant (P<0.05) decrease was observed in n-6 value between the fertilized eggs and the absorbed yolk-sac larvae. It reduced from 17.45% at the fertilized eggs to 10.19% at absorbed yolk-sac larvae. It is considered that the reductions of C18:2n-6, C20:2n-6, C20:3n-6 caused a decrease in total n-6. On the other hand, an increase in arachidonic acid (AA) and docosahexaenoic acid (DHA) give rise to (AA)/eicosapentaenoic acid (EPA) and DHA/EPA ratios in absorbed yolk-sac larvae.
Keywords: Oncorhynchus mykiss; Fertilized eggs; Fatty acids; Rainbow trout; Larvae